Peran Penilai Pbb-P2 Dalam Meningkatkan Penerimaan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Unit Pelayanan Pemungutan Pajak Daerah Wilayah Menteng Jakarta Pusat - Akbar, Renditya; Kertabudi, Indira Santi; Rohmah, Lailatur (Jurnal Pajak Vokasi (JUPASI), 2024)
PBB-P2 plays a crucial role in maintaining the financial sustainability of local governments and ensuring adequate revenue sources to meet community needs. PBB-P2 assessors play a vital role in the assessment process and in the collection of PBB-P2. This study aims to analyze and evaluate the role of PBB-P2 assessors, analyze and evaluate the obstacles faced by assessors, and analyze and evaluate efforts to overcome the inhibiting factors in increasing revenue in the UPPPD Menteng area of Central Jakarta. This research uses a qualitative approach with a descriptive method. The data collection techniques used are interviews with 10 informants, direct observation, and written documents.The research results show that the role of PBB-P2 assessors in increasing PBB-P2 revenue in UPPPD Menteng, Central Jakarta, is quite good and meets the criteria for their role, although some obstacles remain. These obstacles include incomplete and inaccurate property data, insufficient number of assessors, limited quality of assessors due to a lack of advanced education and training programs, limited optimal individual assessments, and lack of cooperation from related agencies. Efforts that can be made by PBB-P2 assessors to overcome these obstacles include conducting socialization and increasing communication with taxpayers, proposing an increase in the number of PBB-P2 assessors, proposing quality improvement through advanced education and training programs, proposing the formation of assessment teams, and enhancing cooperation with related agencies.